Patterns of vitamin D, parathyroid hormone and c-terminal telopeptide of collagen type 1 in Caucasian and African descent HIV-infected populations in Central Europe - Sebastian Noe; Celia Oldenbuettel; Silke Heldwein; Hans Jaeger; Eva Wolf (MDPI AG, 2017)
Risk factors for bone loss in HIV patients might differ or have a different impact in African descent compared to Caucasian populations. The aim of the paper is to analyze the relevance of risk factors on surrogate markers of bone metabolism in HIV-infected African descent and Caucasian patients. This is a cross-sectional study in a single HIV-specialized research and clinical care center in Munich, Germany. We included 889 patients in the study, among them 771 Caucasians (86.7%). Only in Caucasians lower vitamin D levels [OR: 2.5 (95CI: 1.6-3.7)], lower calcium levels [OR: 1.8 (1.2-2.8)], and the use of tenofovir disoproxil fumarate [OR: 2.8 (1.8-4.4)] were significantly associated with elevated PTH in multivariate analysis. Likewise, only in Caucasians elevated PTH was significantly associated with elevated markers of c-terminal telopeptides of collagen type 1 (β-CTX) [OR: 1.7 (1.0-3.0)]. Effects of traditional risk factors for secondary hyperparathyroidism and increased markers of bone turn-over seem to be less distinct in African descent HIV patients. The clinical impact and generalizability of this finding as well as the significance of vitamin D supplementation in African descent patients therefore warrants further investigation.